IMPLEMENTATION OF RELIGIOUS CHARACTER EDUCATION THROUGH ISLAMIC SCHOOL CULTURE - Nastiti, Sekar Arum; Fattah, Abdul (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2023)
The aim of the research is to describe the implementation of religious character education through the culture of Islamic schools in MAN 2 Ponorogo, to analyse the results of the realization of the education of religion through Islamic school culture in MAN 2, and to analyze the obstacles and solutions in implementing religion character education via Islamic culture in the school. The study uses a method of qualitative descriptive approach. Data collection techniques through observation techniques, interviews, and documentation. Data analysis techniques use the data analysis model of Miles and Huberman : data collection, data reduction, data presentation, and conclusion drawings. The results of the study indicate that: (1) Implementation of religious character education through Islamic school culture in MAN 2 Ponorogo covers three stages namely planning, implementation, and evaluation, (2) Implications and solutions in the implementation of religion education through the Islamic culture in school MAN 2 Ponorogo, it’s a weakness of discipline of praying jama’ah, the minimum ability of the students in reading the Qur’an, and lazy students. The dimension of prayer by performing the prayer in time and responsibility. The dimensions of experience with khusyu, in sincerity, and in responsibility in worship. The size of knowledge by applying tajwid knowledge in reading the Qur'an.